(3cJGH aj JGQjN GdOhdI GdYKeGfjIs
(3ChdgG (B:s
(3aj GdcdGe Ydi GdOhdI GdYKeGfjI ef SfI(B1200 (3Edi SfI (B1520 (3ef GdejdGO CYde Gfg HYO Cf NdG cQSi NhGQRe ef BNQ SdGWjfgG GdPi bgQg LfcjR NGf ONd HYV ef cGf eSJNOekG YfO Pdc GdSdWGf s
(3BNQgG (B:s
(3aEf ChdGO GdSdWGf MjK Efge fTChG aj XdGd GdSQGjI HYjOjf Yf GdeYScQGJ RGdJ Yfge YhGFO CSdGage GdMQHjI hHYO Cf cGfJ GdOhdI GdYKeGfjI eDSSI Ydi GdaJhM CNPJ aj GdEfMWGW hGdSbhW s
(3Vef eLehY , JQJjHgG (B: (3ef U (B127 - (3U(B163s
(3ef SfI (B1200: (3SfI (B1520 (3es
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B338 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(1065 (3O(B) s
Keywords: (3GdJGQjNs